Psychometric Properties of Geriatric Depression Scale in an Iranian Sample - zahra Amini Rastabi; Ali Akbar Sharifi; Jaleh Refahi (University of Social Welfare & Rehabilitation Sciences, 2013)
Objectives: This study aimed to Examine psychometric properties of and geriatric depression scale. Methods & Materials: Method of This study is descriptive. Statistical population includes all aged over 60 years in the retirement centers of organizations and Nursing homes in shahrekord. 380 persons (113 females and 267 males) were selected through stratified random sampling method. In order to collect data, geriatric depression scale (Yesavage et al., 1982) and Composite International Diagnostic Interview (WHO, 1990) was used. Results: The results of the present study indicate satisfactory reliability and‬‬ ‫‪internal consistency and Cronbach’s alpha and Spearman split test was estimated 0.75 and 0.77 respectively. Also The ROC analysis showed that the best cutoff score for this scale is 16.5 with sensitivities of 0.88 and specificities of 0.87. Conclusion: The results showed that geriatric depression scale is a valid and reliable instrument and it can be used for diagnosing depression in the elderly.